AN INVESTIGATION OF PHYLOGENETIC RELATIONSHIPS OF POPULATIONS OFARTEMISIA TAURICA Willd. (ASTERACEAE) FROM TURKEY USING trn REGIONS - Sancar, Pelin Yilmaz; Delipoyraz, Sueda; Civelek, Semsettin; Kursat, Murat (Pakistan Botanical Soc, 2022)
Artemisia L. is one of the biggest genera in the family Asteraceae, with around 500-600 taxa at specific and sub -specific levels diveded in five subgenera. The majority of the members of this genus have a high economic value. Due to the high number of taxa, lot of taxonomists are tried to solve the problem of its classification and phylogeny but its natural classification still has not been achieved. In order to find the phylogenetic relations and kinships between individual samples, the present study investigated the base polymorphisms in sequences of non -coding trnT-trnL3' section of chloroplast DNA (cpDNA) of 54 individual samples of 22 different populations belonging to A. taurica Willd. in Turkey. DNA was isolated from the leaves of the studied individual samples by the CTAB method, and isolated genomic DNA was multiplied in PCR by using trna and trnd primaries of the trnT-trnL3' section. The obtained data were evaluated by the Mega X program, and phylogenetic trees were prepared by using the Maximum Likelihood method. There are no molecular significant differences between populations of the species A. taurica in Turkey depending on absence of genetic isolation and still ongoing gene. The view that the morphological differences observed on the samples of the Zernek dam lake (Van) population of the species A. taurica were found to be related to the ecological conditions and ploidy level.
Keywords: Asteraceae; Artemisia taurica; cpDNA trn T - trn L3'; Phylogeny; PCR